Reforming the global monetary non-system - José Antonio Ocampo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper proposes a comprehensive yet evolutionary reform of the global monetary non-system that evolved out of the breakdown of the original Bretton Woods arrangement in the early 1970s. It includes: (i) a global reserve system that mixes the multi-currency arrangement with an active use of the International Monetary Fund's Special Drawing Rights; (ii) stronger mechanisms of macroeconomic policy co-operation, including management of the exchange rate system and capital account regulations; (iii) additional automatic balance-of-payments financing facilities, and the complementary use of swap and regional arrangements; (iv) a multi-lateral sovereign debt workout mechanism; and (v) major reforms of the system's governance.
Keywords: F02; F33; F36; 330; reserve; urrencies; macroeconomic co-operation; balance-of-payments financing; sovereign debt workouts; global governance